Analisis Kadar Hidrokuinon pada Day cream yang Beredar di Kecamatan X Kabupaten Sukoharjo - Kharisma Riskiana; Danang Raharjo (Pusat riset dan Inovasi Nasional, 2026)
The use of cosmetics, especially day creams, is increasing along with the high public interest in facial skin care. However, day cream products are still found to potentially contain hydroquinone, a skin whitening agent whose use is restricted because it can cause harmful side effects on skin health. This study aims to identify the presence and determine the levels of hydroquinone in day cream products circulating in District X, Sukoharjo Regency, and to assess their compliance with the regulations of the Food and Drug Monitoring Agency (BPOM). This study was a descriptive analytical study using a purposive sampling technique. A total of 15 day cream products were analyzed, consisting of 8 BPOM-registered products and 7 products not registered with BPOM. Qualitative analysis was conducted using color reaction tests with FeCl₃, Benedict’s, and o-phenanthroline reagents. Furthermore, quantitative analysis was performed using the High Performance Liquid Chromatography (HPLC) method to accurately and specifically confirm the presence and determine the levels of hydroquinone. The results showed that the color reaction test has limitations in specifically identifying hydroquinone. HPLC confirmation revealed the presence of hydroquinone in several day cream samples, with concentrations ranging from 0.024% to 0.150%. These findings indicate the need for stricter monitoring of day cream distribution to ensure the safety of cosmetic products for the wider public.